2019
DOI: 10.11604/pamj.2019.33.252.15781
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of syphilis in HIV-seropositive patients: a retrospective study at the regional hospital in Agadir, Morocco

Abstract: IntroductionHIV and syphilis are major public health problems in Morocco. The region of Souss-Massa, south-west of the country, hold more than 24% of HIV seropositive cases registered in Morocco during 2009. The aim of this study is to evaluate the seroprevalence of syphilis among HIV seropositive patients in the region of Souss-Massa, south-west of Morocco.MethodsTo evaluate the seroprevalence of syphilis and neurosyphilis among HIV seropositive patients, we retrospectively investigated the medical records of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…It is encouraging that the reported prevalence of syphilis in this study is similar to the prevalence of syphilis among PLHIV reported in Ethiopia [ 23 ]. Although the prevalence of syphilis in our study may have been overestimated due to the limitations of the test kits in reacting to non-treponemal infections, studies in other African countries such as Nigeria (14.0%), Ghana (14.8%), Morocco (16.4%), Chad (14.0%), and Tanzania (9.6%) reported a higher prevalence [ 8 10 , 24 26 ]. The disparities in these findings may be due to the different composition of the study populations and differences in the methods applied for the detection of syphilis or perhaps may reflect the variations in the risky behavioral practices across the African region.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…It is encouraging that the reported prevalence of syphilis in this study is similar to the prevalence of syphilis among PLHIV reported in Ethiopia [ 23 ]. Although the prevalence of syphilis in our study may have been overestimated due to the limitations of the test kits in reacting to non-treponemal infections, studies in other African countries such as Nigeria (14.0%), Ghana (14.8%), Morocco (16.4%), Chad (14.0%), and Tanzania (9.6%) reported a higher prevalence [ 8 10 , 24 26 ]. The disparities in these findings may be due to the different composition of the study populations and differences in the methods applied for the detection of syphilis or perhaps may reflect the variations in the risky behavioral practices across the African region.…”
Section: Discussionmentioning
confidence: 59%
“…However, the global effort to eliminate syphilis as a major public health problem by 2030 is hampered by several challenges facing the health system in low-income countries [ 7 ]. Consequently, many studies in low-income countries have shown high rates of syphilis among PLHIV, reinforcing the need for robust syphilis screening programs in sub-Saharan Africa [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite The World Health Organization’s strategic goal of reducing syphilis incidence by 90% by 2030, 5 this goal is a long way off today, given the data from some at-risk groups. 6,18,19…”
Section: Discussionmentioning
confidence: 99%
“…Despite The World Health Organization's strategic goal of reducing syphilis incidence by 90% by 2030, 5 this goal is a long way off today, given the data from some atrisk groups. 6,18,19 Early diagnosis and treatment of syphilis are very effective strategies for prevention and control of the disease at both the individual and community levels. 20 However, the clinical diagnosis of syphilis can be challenging and misdiagnosis is common because the infection can mimic many other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Shows comparison with different studies[8,[21][22][23][24].Also, a 23% HIV-syphilis co-prevalence rate were seen in a populationbased study in HIV positive Andhra Pradesh, India[25].Bourouache M et al, reported in their study that syphilis was prevalent in 16.42% in Morocco[26].Haule A et al, reported a prevalence of syphilis in HIV-infected patients of 9.6% in Tanzania[27]. Santos AM et al, reported a prevalence of 18.4% among HIV-infected patients in Brazil[28].Khan S et al, reported a prevalence of 6.5% syphilis among the HIV-positive individuals screened for syphilis in South India between…”
mentioning
confidence: 84%